The Influence of Management Control Systems and Balanced Scorecard on Strategic Decision Making: The Moderating Role of Information Technology (A Study of Private Universities in Medan City) - Martin, Martin; Andira, Ayu; Nasution, Mardiah Hasanah (Journal Of Accounting Management Business And International Research, 2025)
This study aims to analyze the effect of Management Control Systems (MCS) and Balanced Scorecard (BSC) on Strategic Decision Making (SDM), with Information Technology (IT) as a moderating variable in Private Universities (PTS) in Medan City. The background of this study is based on the need for higher education institutions to adapt to the dynamics of globalization and digitalization, which require performance and information-based governance. A quantitative approach was used with the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method on 251 managerial leaders as respondents. The results show that both MCS and BSC have a significant effect on SDM. MCS has a direct positive effect on PKS, but indirectly through IT, it shows a negative direction, indicating that overly rigid control systems can hinder the utilization of technology. Conversely, BSC has a significant and positive effect on IT and PKS, both directly and indirectly, indicating that BSC is capable of improving the quality of strategic decisions through the strengthening of information systems. In addition, IT proved to be a significant mediating factor in strengthening the relationship between variables, with the model's predictive contribution reaching 95.4%. This study emphasizes the importance of adaptive and integrative management system design, as well as the optimal use of information technology in supporting strategic decision-making in the higher education sector. These findings have theoretical implications for the development of modern management accounting literature and practical implications for PTS leaders to develop data-driven strategies and technological innovations.